PENYULUHAN PENTINGNYA PENCEGAHAN DAN PENGOBATAN PENYAKIT HIPERTENSI GUNUNG TERANG RT. 03 LK I WILAYAH KERJA PUSKESMAS KEMILING BANDAR LAMPUNG - Iskandar Iskandar; Winda Restu Anggraini; Budi Rahman (Holistik Jurnal Kesehatan, 2019)
Psychiatric inpatients' perceptions of positive and negative aspects of physical restraintBackground: Restrain carried out on mental hospital clients also has a negative impact, besides restrain also has a positive impact that clients are calmer, reduce risk hurt himself. Restrain the client can cause physical impacts on the client, edema, lesions, the risk of injury, incontinence, the appearance of the client is less neat, and often the basic human needs of the client are not met. In addition, clients also feel the psychological effects of anxiety, anger, fear and even physical and psychological trauma.Purpose: To identify Psychiatric inpatients' perceptions of positive and negative aspects of physical restraint at Atma Husada Mahakam Hospital of Province East Kalimantan.Methods: This study uses quantitative research methods with designs descriptive, the sample of the study was 46 respondents and the data collection in the form of a questionnaire lately was about the physical impact and psychological impact.Results: The results of the study the majority of respondents 37 people (72.5%) experienced physical impact in the category of positive impact. While the study of the majority of respondents 28 people (60.9%) experienced a psychological impact on the positive impact category.Conclusion: Physical impact on restrain action is more dominant in the impact category, while the psychological impact on restrain action is more dominant in the positive impact category. It is recommended that nursing service agencies, can foster nurses' confidence to improve management of restrain measures.Keywords: Psychiatric inpatients; Perceptions; Physical restraint; Violent behaviorPendahuluan: Restrain yang dilakukan pada klien di rumah sakit jiwa ternyata juga menimbulkan dampak negatif, selain itu restrain juga memiliki dampak positif yaitu klien jadi lebih cepat tenang, mengurangi risiko mencederai diriya sendiri. Restrain pada klien bisa menyebabkan dampak fisik bagi klien yaitu oedema, lesi, resiko terjadi cedera, inkontensia, penampilan klien kurang rapi, dan sering kali kebutuhan dasar manusia pada klien tidak terpenuhi. Selain itu klien juga merasakan dampak psikologis yaitu cemas, marah, takut bahkan trauma baik fisik maupun psikologis.Tujuan: Mengidentifikasi gambaran dampak tindakan restrain pada klien dengan gangguan jiwa di RSJD Atma Husada Mahakam Propinsi Kalimantan Timur.Metode: Penelitian ini menggunakan metode penelitian kuantitatif dengan desain deskriptif , sampel penelitian sebanyak 46 orang responden dan alat pengumpulan data berupa kuesioner berisi tentang dampak fisik dan dampak psikologis.Hasil: Hasil penelitian mayoritas responden 37 orang (72.5%) mengalami dampak fisik pada kategori dampak positif. Sedangkan penelitian mayoritas responden 28 orang (60.9%) mengalami dampak psikologis pada kategori dampak positif.Simpulan : Dampak fisik pada tindakan restrain lebih dominan pada kategori dampak, sedangkan dampak psikologis pada tindakan restrain lebih dominan pada kategori dampak positif. Disarankan agar instansi pelayanan keperawatan, dapat menumbuhkan rasa percaya diri perawat untuk meningkatkan penatalaksanaan tindakan restrain. untuk meningkatkan pengetahuan dan dalam menjalankan penatalaksanaan tindakan restrain.